2019
DOI: 10.1021/acs.iecr.9b00739
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Hematite: An Efficient Photoanode for Photoelectrochemical Water Splitting

Abstract: Photoelectrochemical water splitting has gained considerable interest in the past few decades because of its potential for harvesting solar light for H 2 production. For harvesting solar light, the design of a semiconductor photoelectrode is the critical parameter to control performance. In this regard, vertically aligned, interconnected 2D nanosheets of α-Fe 2 O 3 show the most efficient activity for PEC water splitting as compared to other morphologies like thick sheets and nanorods as the former absorb more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…where C = specific capacitance, ε = dielectric constant of the semiconductor, N d = carrier density, V FB = flat band potential, e = electron charge, A = area of the sample, ε 0 = electric permittivity of vacuum, T = temperature, and k = Boltzmann constant. 53 The slopes of ZnO/C study of ZnO/C 3 N 4 QDs with similar photoanodes, which is reported in the literature, is shown in Table S2.…”
Section: ■ Photoelectrochemical Activitymentioning
confidence: 64%
See 1 more Smart Citation
“…where C = specific capacitance, ε = dielectric constant of the semiconductor, N d = carrier density, V FB = flat band potential, e = electron charge, A = area of the sample, ε 0 = electric permittivity of vacuum, T = temperature, and k = Boltzmann constant. 53 The slopes of ZnO/C study of ZnO/C 3 N 4 QDs with similar photoanodes, which is reported in the literature, is shown in Table S2.…”
Section: ■ Photoelectrochemical Activitymentioning
confidence: 64%
“…The n-type nature of the designed electrodes is confirmed by the positive slope of the M–S plot. The carrier densities are calculated from the following equation: where C = specific capacitance, ε = dielectric constant of the semiconductor, N d = carrier density, V FB = flat band potential, e = electron charge, A = area of the sample, ε 0 = electric permittivity of vacuum, T = temperature, and k = Boltzmann constant . The slopes of ZnO/C 3 N 4 -15 and -30 are smaller than that of bare ZnO, which indicate the enhanced carrier density after sensitization of C 3 N 4 .…”
Section: Photoelectrochemical Activitymentioning
confidence: 99%
“…It has been identified that twodimensional (2D) ZnO and Fe 2 O 3 show optimal behavior as photoanodes for PEC water splitting due to having such interesting advantages. 14,15 Furthermore, to cope with the disadvantages of ZnO, several methods have been undertaken such as introducing defects, dopants, and sensitization by narrow band gap quantum dots such as CdSe, PbS, CdS, and plasmonic nanoparticles. 16−18 These methods have been identified to boost the optical absorption and improve the photogenerated charge carrier separation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They can decouple the path of light absorption and charge-carrier transportation and are able to provide an enormous number of surface-active atoms for the electrochemical reaction. It has been identified that two-dimensional (2D) ZnO and Fe 2 O 3 show optimal behavior as photoanodes for PEC water splitting due to having such interesting advantages. , Furthermore, to cope with the disadvantages of ZnO, several methods have been undertaken such as introducing defects, dopants, and sensitization by narrow band gap quantum dots such as CdSe, PbS, CdS, and plasmonic nanoparticles. These methods have been identified to boost the optical absorption and improve the photogenerated charge carrier separation. A good sensitizer must have the following properties to improve the PEC water-splitting reaction: (1) it should have the ability to increase the optical absorption of the semiconductor material, (2) the band alignment of the sensitizer and the semiconductor should allow suitable charge carrier separation, and (3) it must have long-term resistance to corrosion during the PEC water-splitting reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier concentrations and electronic properties of the ZnO thin sheets and Au NPs decorated on ZnO are determined using the Mott–Schottky plots and displayed in Figure d. The carrier density is calculated using the equation 1/ C 2 = (2/ e εε 0 N d A 2 )­[( V – V FB – kT )/ e ]. , Here, N d , C , ε 0 , e , ε, T , A , V FB , and k represent the charge-carrier density, specific capacitance, electric permittivity of vacuum, electron charge, dielectric constant of the semiconductor, temperature, area of the sample, flat band potential, and Boltzmann’s constant, respectively. An observed positive slope indicates the n-type nature of the developed electrodes.…”
Section: Pec Activitymentioning
confidence: 99%